Gabon : Assessment of the Impact of Tobacco Excise Tax Increases on Price, Consumption and Tax Revenue over 2018-2021 - World Bank Group (World Bank, Washington, DC, 2019)
This country report assesses the impact of tobacco tax policy increases on prices, consumption, and fiscal revenue. The scientific evidence accumulated over the past five decades is clear: tobacco kills. Smokers who begin early in adult life and do not stop smoking face a three-fold higher risk of death compared to otherwise similar non-smokers, resulting in a loss, on average, of at least one decade of life (Jha and Peto 2014). Smoking is the second-leading cause of death globally (GBD 2015 Collaborators). Both active smoking and exposure to secondhand smoke cause disease and kill prematurely (Marquez and Moreno-Dodson 2017). More than 7 million people die from tobacco use every year, a figure that is predicted to grow to more than 8 million a year by 2030, in the absence of intensified global action (WHO 2017). Annually, the number of deaths from tobacco-attributable diseases exceeds the deaths from HIV/AIDS, tuberculosis, and malaria combined (WHO 2008). Most of these deaths are due to direct tobacco use, while close to 10 percent of deaths are the result of non-smokers’ exposure to secondhand smoke. Developing countries and vulnerable groups face health risks associated with tobacco use, and with e-cigarettes. Low- and middle-income countries (LMICs) face an increasing burden of noncommunicable diseases (NCDs), which are now the leading cause of death in the world, killing 40 million people each year and representing 70 percent of all annual deaths (WHO 2018). Eighty percent of deaths due to tobacco-related NCDs—cancer, cardiovascular disease, chronic lung disease, and diabetes— occur in LMICs, straining health care systems, contributing to poverty, and posing a major barrier to development. An estimated 40 percent of the global economic costs of tobacco use are already borne by these countries, and there is a risk that the costs will escalate if effective and sustained tobacco control action is not supported over the short and medium term. In Gabon, according to available data from the Demographics and Health Survey (DHS), it is estimated that among people aged 15-49 years old, the prevalence of smoking was 22.3 percent among men and 2.9 percent among women. This prevalence of smoking was found to be the highest among the countries which conducted DHS in the African region. In Gabon, tobacco use is among the ten leading risk factors that drive the most death and disability (IHEM 2017).